Understanding Student Struggles: The Phenomenon of Objectification in Indonesian Online Education During the COVID-19 Pandemic - Muassomah Muassomah; Irwan Abdullah; Na’imah Na’imah; Khairiah Khairiah; Demina Demina; Asyifa Nadia Jasmine (COVID, 2025)
Online learning during the COVID-19 pandemic has positioned students as objects. They are not given a position as subjects in the teaching–learning process. The policies of the online education system have forced students to lose their rights to negotiate and interact with teachers and friends. They are required to comply with all applicable regulations in their schooling during the COVID-19 pandemic. This paper maps the objectification aspects experienced by students during online education, including the types of burdens experienced during the learning process, as well as learning evaluations that are not optimal. The qualitative method used in this paper relies on data from interviews with 30 elementary school students. The results of this paper show that the online education system during the pandemic has positioned children as passive objects who only accept the decisions of adults, depriving them of opportunities to ask questions or engage in discussions with their teachers and peers. Children were expected to adhere to all predetermined policies without being given a platform to express their perspectives. This paper concludes that learning in the time of COVID-19 has taken away the ideal meaning of education for students, which should have been realized and safeguarded according to the expected goals.